The Relationship Between Morphology, Morphogenesis and Morphotectonics Potential for Flood Disasters in the Karanggayam Area, Kebumen Regency, Indonesia - Retongga, Nofrohu; Razi, Muhammad Haikal (Politeknik Negeri Batam, 2024)
The Regional Disaster Management Agency (BPBD) of Kebumen Regency recorded that from 2011 to 2020 there were 1,335 disaster events, 154 (11.5%) of which were flood disasters. There were eight flood disasters in Karanggayam District were 8 incidents. This research method consists of four stages: literature study, field observation and mapping, analysis of morphology, morphogenesis, and morphotectonics, and analysis of the relationship between morphology, morphogenesis, morphotectonics, and flood potential. The potential for flood disasters is related to the morphological aspects, morphogenesis, and morphotectonics as controlling factors for flood disasters in the research area. Based on the potential for flood disasters in the research area, it is necessary to carry out non-structural mitigation in the research area. Appropriate nonstructural mitigation of flood disasters based on field facts, such as installing an early warning system for flood disasters, having evacuation routes and signs pointing to evacuation routes, socializing flood disasters, and installing warning boards in areas prone to flood disasters to minimize the risk of flood disasters in the Karanggayam area.